Fish Consumption and Hair Mercury Among Asians in Chicago. Issue 12 (December 2015) - Buchanan, Susan; Targos, Loreen; Nagy, Kathryn L.; Kearney, Kenneth E.; Turyk, Mary
Abstract : Objectives: The aim of the study was to characterize the risk for elevated mercury (Hg) from fish consumption among Asians in Chicago. Consumption of fish contaminated with methyl Hg (MeHg) can affect the neurodevelopment in children and cardiovascular disease risk in adults. Methods: We collected fish consumption information and hair samples for Hg at two health fairs. We purchased fish from Asian fish markets. Results: Geometric mean hair Hg from 71 participants was 0.58 μg/g, with 28% overall and 29% of women of childbearing age having hair Hg levels at least 1 μg/g; 20% ate fish 4 or more times/wk. Tuna consumption and non-Chinese Asian ethnicity were associated with elevated Hg. Hg levels in purchased fish were generally low. Conclusions: Our study confirms other findings that, compared with estimates of the general US population, Asians are at higher risk of elevated MeHg because of frequent fish consumption.